Longevity and survival of Leptocybe invasa (Hymenoptera: Eulophidae), an invasive gall inducer on Eucalyptus, with different diets and temperatures - Amanda Rodrigues De Souza; Leonardo Rodrigues Barbosa; José Raimundo de Souza Passos; Bárbara Monteiro de Castro e Castro; José Cola Zanuncio; Carlos Frederico Wilcken (PeerJ, 2018)
The blue gum chalcid, Leptocybe invasa Fisher & LaSalle (Hymenoptera: Eulophidae), causes galls on Eucalyptus spp. leaf midribs, petioles and stems. Biological aspects need to be studied to assist in developing management strategies and to maintain this insect in the laboratory to rear the parasitoid Selitrichodes neseri Kelly & La Salle (Hymenoptera: Eulophidae) that depends on having a supply of Eucalyptus seedlings infested by L. invasa. We evaluated the longevity and survival of L. invasa individual non reproductive females fed with six different diets (pure honey, 50% honey solution, pure honey plus eucalyptus leaves, eucalyptus leaves, distilled water, or no food) and seven different temperatures (10, 14, 18, 22, 26, 30 and 34 °C). Leptocybe invasa fed with 50% honey solution and reared at 14 or 18 °C showed the greatest longevity and survival.